Regular football training down-regulates miR-1303 muscle expression in veterans - Mancini, A.; Vitucci, D.; Orlandella, F. M.; Terracciano, A.; Mariniello, R. M.; Imperlini, E.; Grazioli, E.; Orrù, S.; Krustrup, P.; Salvatore, G.; Buono, P. (European journal of applied physiology, 2021)
Purpose Regular exercise affects the expression of several genes, proteins and microRNAs (miRNAs) in time- and intensity-dependent manner promoting longevity. We previously identified from GeneChip Array analysis several differentially expressed genes and miRNAs in muscle from veteran football players (VPG) compared to active untrained elderly subjects (CG); here we focussed on miRNA-1303 (miR-1303). The aims of the present research were: to analyse the effects of football training on the expression of miR-1303 and to identify its putative target involved in the longevity pathways in skeletal muscle from VPG compared to CG. Methods RNA samples from 12 VPG and 12 CG muscle biopsies were used to validate miR-1303 expression. Crossing four different bioinformatic algorithms, we identified 16 putative targets of miR-1303; from these, BAG-2, KLHL7 and KBTBD6 were chosen for further validation by Western blot analysis in LHCN-M2 human myoblasts transiently transfected with miR-1303. Results Football training down-regulates miR-1303 expression in muscle from VPG compared to CG and the expression of BAG-2, a chaperon protein involved in the autophagy pathway, inversely correlated to overexpression of miR-1303 in a time-dependent manner, indicating that it is a miR-1303 potential target. Conclusions This is the first report, to our knowledge, describing miR-1303 regulation in skeletal muscle by football training and the identification of a target protein, BAG-2, involved in the autophagy pathway. This result contributes to the enlargement of knowledge on the molecular mechanisms linking football training, autophagy and longevity.